Antiplatelet therapy discontinuation and stent thrombosis after sirolimus-eluting stent implantation: Five-year outcome of the j-Cypher Registry. (15th November 2015) - Yano, Mariko; Natsuaki, Masahiro; Morimoto, Takeshi; Nakagawa, Yoshihisa; Kawai, Kazuya; Miyazaki, Shunichi; Muramatsu, Toshiya; Shiode, Nobuo; Namura, Masanobu; Sone, Takahito; Oshima, Shigeru; Nishikawa, Hideo; et al.
Abstract: Background: The influence of antiplatelet therapy discontinuation on the incidence of stent thrombosis, especially very late stent thrombosis, after drug-eluting stent implantation has not been yet fully addressed. Methods: Relationship between antiplatelet therapy discontinuation and stent thrombosis up to 5 years was evaluated in 12, 812 consecutive patients undergoing sirolimus-eluting stents (SES) implantation in the j-Cypher registry. Data on status of antiplatelet therapy during follow-up were collected prospectively. Results: Median follow-up interval was 1699 days (interquartile range, 1184–1928 days). Incidences of definite stent thrombosis were 0.34% at 30 days, 0.55% at 1 year, and 1.6% at 5 years. Dual antiplatelet therapy was maintained in 97.4%, 63%, and 43.9% of patients at 30 days, 1 year, and 5 years, respectively. The rates of stent thrombosis in patients who discontinued both thienopyridine and aspirin were significantly higher in the time intervals of 31–365 days, 2–3 years and 3–4 years, and tended to be higher in the time intervals of 1–2 years and 4–5 years than those in patients who continued both (31–365 days: 1.26% versus 0.2%, P < 0.001; 1–2 years: 0.59% versus 0.15%, P = 0.06; 2–3 years: 1.35% versus 0.2%, P = 0.004; 3–4 years: 1.09% versus 0.25%, P = 0.0496; 4–5 years: 1.35% versus 0.43%, P = 0.17). Patients who discontinued either thienopyridine or aspirin only did not have an excess of stent thrombosis in any time intervals. Conclusions: In conclusion, discontinuation of both thienopyridine and aspirin, but not discontinuation of thienopyridine or aspirin only, was associated with an increased incidence of late and very late stent thrombosis up to 5 years after SES implantation. Highlights: It is unknown whether discontinuation of both thienopyridine and aspirin could be excess risk for ST long after SES implantation. Discontinuation of both antiplatelet agents was associated with an increased incidence of ST after SES implantation. Discontinuation of either thienopyridine or aspirin only was not associated with higher incidence of ST.